IMPROVING EFL LEARNERS’ SPEAKING SKILL THROUGH THE USE OF CODE SWITCHING STRATEGIES IN THE CONVERSATION - Syamsudin Syamsudin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study is about code switching strategies usage as a part of communication strategies used by the EFL learners in Higher Education to improve their speaking skill. This paper presents the discussion on code switching strategies usage employed by two EFL learners to improve their speaking skill. This topic is interesting to be discussed because the employment of code switching strategies during the conversation might facilitate EFL learners to learn speaking. This happens due to the opportunity of the EFL learners to use L1 to express some unfamiliar vocabularies during the conversation. Further, byemploying code switching strategies in conversation learners might feel comfortable so that they have courage and self confidence to practice speaking. Thus, it is crucial for the EFL learners to use code switching strategies in the process of learning speaking so that they might improve their speaking ability.